Neurocognitive and neuroanatomical changes in children with acute lymphoblastic leukemia treated with the modified BFM-95 protocol - Sundaramoorthy Chidambaram; Vidhubala Elangovan; Vandana Mahajan; Prasanth Ganesan; Venkatraman Radhakrishnan (Indian Journal of Medical and Paediatric Oncology)
Background: The use of cranial radiotherapy for central nervous system (CNS) prophylaxis in children with acute lymphoblastic leukemia (ALL) is debated owing to its effect on neurocognitive functioning, as only <30% of the patients present with low risk in India and majority of the patients with high risk have to be treated with cranial radiation therapy (CRT) to prevent relapse. Given the increasing number of ALL survivors in India, the effect of CRT on neurocognitive functioning in children with ALL needs to be studied. Methods: Children (n = 44) with ALL who received CRT, intrathecal methotrexate (IT-MTX), and high-dose methotrexate (HD-MTX) for CNS prophylaxis as part of the modified Berlin-Frankfurt-Munster 95 protocol were included. Neurocognitive assessments and magnetic resonance image were performed to assess neurocognitive functioning and neuroanatomical structures, respectively. Five assessments were performed during the induction, end of re-induction I and II, commencement of maintenance, and end of maintenance phases of the modified BFM-95 protocol. Neurocognitive data of children with ALL were compared with those of healthy children (n = 60) at the baseline and after the final assessment. Results: A significant deterioration was observed in the performance intelligence, visuospatial ability, processing speed, and verbal retention domains after the completion of CNS prophylaxis. Three children had white matter changes on magnetic resonance imaging and showed reduced functioning in performance intelligence quotient, working memory, visual immediate and delayed memory, processing speed, verbal retention, visuospatial ability, processing speed, attention, planning and fine motor skills, and verbal comprehension. Children with ALL had poorer neuropsychological functioning when compared with healthy children. Conclusion: CNS prophylactic therapy as part of the BFM-95 protocol had an adverse effect on the neuropsychological functioning of children with ALL, and the effect was more pronounced when CRT was added to the treatment.